The Purmamarca area, eastern cordillera, Jujuy province - Ortega, Gladys del Carmen (2003)
The Purmamarca village is placed ca 50 km to northwest of Jujuy City, on the western side of the Quebrada de Humahuaca, Tumbaya Department, Jujuy Province (Figure 5). Within the general context of the Quebrada de Humahuaca, it is one of the most picturesque areas of the Argentina for tourism, and was recently declared by UNESCO cultural heritage of the humanity. From a geological point of view, it is a classical locality for the study of lower Paleozoic rocks of the Eastern Cordillera (e.g., Keidel, 1917; Kobayashi, 1936, 1937; Harrington, 1938; De Ferrariis, 1940; Harrington & Leanza, 1957; Ramos et al., 1967; Rao et al., 1994; Tortello, 1996; Tortello & Aceñolaza, 1999). Graywakes, quartzites and slates of the Puncoviscana Formation (Upper Precambrian – Lower Cambrian) constitute the basement of the Eastern Cordillera. Ichnofossils of Vendian/Tommotian age were recorded in this formation by Aceñolaza et al. (1999). These authors described the ichnogenusProtichnites from strata of the Puncoviscana Formation exposed at Purmamarca (Aceñolaza et al., 1999). The dominantly sandstone sequences of the Mesón Group (Lower Cambrian), unconformably overlie the Puncoviscana Formation (Tilcara unconformity) (Turner & Méndez, 1975; Moya, 1999). The Iruya unconformity (Turner, 1960) separates the successions of the Mesón Group from the Lower to Middle Ordovician Santa Victoria Group (Santa Rosita and Acoite formations) (Turner, 1960), and equivalent units.